The needs of traumatic brain injury survivors' caregivers and the implication required during the COVID-19 pandemic: public health issues - Othman, Hamidah; Mohamed Ludin, Salizar; Saidi, Sanisah; Awang, Mohamed Saufi (Page Press Publications, 2021)
Background: Traumatic brain injury (TBI) survivors require attention and dependence from their primary caregiver. This is because TBI is a defect that affects both the psychological and physical functions of the victim. Caregivers play an essential role in providing the adequate care victims need to adjust to the new problems they may experience due to their condition, as family members alone may not be able to provide for their needs. In particular, TBI caregivers may face specific challenges when assisting their patients in handling unexpected changes to their daily routines. Therefore, this quantitative study aims to explore the needs of caregivers, their coping mechanisms towards stressful and traumatic circumstances, and how they provide care to their loved ones during the COVID-19 pandemic. Design and Methods: It was conducted with ten caregivers of individuals suffering from traumatic brain injury, that were selected using a theoretical sampling method. Data were obtained using a semi-structured interview guide, which helped the caregivers provide their responses. Meanwhile, data analysis was performed using the NVIVO analysis software. Results: The results showed that there were, three significant themes namely, (a) Support needed, (b) the information need for care, and (c) developing self-resilience. The results also showed that caregivers really need support from the various parties, and the participants lack information on specific care techniques for the severe traumatic brain injury (TBI) survivors. Conclusions: In conclusion, caregivers require approval and seek more useful information to provide excellent care to their loved ones. Being aware of the caregiver’s needs would enable them to offer improved customized care.